Analysis of Robotic Procedural Times Using Colpassist Versus End-to-End Anastomosis Sizer for Robotic-Assisted Sacrocolpopexy: A Randomized Controlled Trial. Issue 2 (March 2019) - Brueseke, Taylor; Matthews, Catherine; Willis-Gray, Marcella; Knight, Sean; Nieto, Maria Luz; Geller, Elizabeth
Abstract : Objective: The impact of vaginal instrumentation on operative time for robotic-assisted sacrocolpopexy (RSC) is not well understood. Colpassist (Boston Scientific, Quincy, Mass) is a vaginal positioning device designed to improve exposure with a curved double-sided handle that can be adapted to patient anatomy with 2 different sized functional ends. We sought to compare operative time for RSC using a Colpassist compared with a traditional end-to-end anastomosis sizer (EEAS). Methods: This was a single-center randomized controlled trial of consecutive women undergoing RSC for apical pelvic organ prolapse. Participants were randomized to undergo RSC using either Colpassist or EEAS. The primary outcome was total operative time for the steps of RSC requiring use of a vaginal positioning device. Secondary outcomes included injury rates and satisfaction of the participants. Results: Fifty-two women were enrolled (25 Colpassist, 27 EEAS). For the primary outcome, there was no significant difference in total operative time between procedures performed with Colpassist versus EEAS ( P = 0.15). However, 16 (64%) of the 25 Colpassist arm versus 0 of EEAS ( P < 0.01) required use of an alternative vaginal positioning device intraoperatively. Comparing secondary outcomes, there were no differences in rate of intraoperative injury between groups. Surgeon and fellow satisfaction scores were lower with Colpassist ( P < 0.01). Surgical vaginal assistants were equally satisfied with both vaginal positioning devices ( P > 0.05). Conclusions: Colpassist is a potential alternative to EEAS with no significant difference in operative time or complication rate. However, case completion with Colpassist was significantly lower than EEAS and was associated with lower surgeon and fellow satisfaction.